Jesus in history an approach to the study of the gospels - Kee, Howard Clark (New York, NY Harcourt brace Jovanovich, 1977)
Includes bibliographical references and index.
Keywords: Jesus Christ -- historicity; Bible. N.T. Gospels -- criticism, interpretation, etc; Bible. N.T. Gospels -- history of contemporary events